(untitled) (Research, Society and Development, 2023)
Plants host a great diversity of life, among which are included endophytic fungi, which there are still no reports in the literature about their occurrence on Marajó Island, as well as established interactions between endophyte and host are not yet fully known. For this reason, the purpose of this work was to carry out a survey of the endophytic community that colonizes the plant tissues of Avicennia sp. (black mangrove) and Rhizophora sp. (red mangrove) present at Resexmar de Soure-Pa. For the isolation of these fungi, collections were carried out in the dry season and in the rainy season; healthy leaves were collected and directed to laboratory disinfection. The samples were washed in running water and neutral detergent, subsequently inserted in 70% alcohol, followed by 2.5% sodium hypochlorite, again in 70% alcohol, and finally in distilled water, all immersions lasted 1 minute. After the procedure, the material was directed to the biosafety cabin for isolation in PDA culture medium and stored at room temperature for seven days. Subsequently, the fungal colonies were identified at the genus level through macroscopic analysis of the plates and microscopic analysis of the slides. From the analysis, 242 fungal colonies were observed and 10 endophytic genera were identified: Alternaria sp; Aspergillus sp; Colletotrichum sp; Curvularia; Fusarium sp; Geotrichum sp; Penicillium sp; Purpureocillium sp, Rhizopus sp and Trichoderma sp. In view of this, the presence of endophytic fungi inhabiting mangrove plants at Resexmar Soure was verified, which are widely reported as endophytic in several studies in Brazil.